THE EFFECT OF USING DIFFERENT UREA NORMS IN SUSPENSION METHOD ON BIOMETRIC INDICATORS OF SOYBEAN - Umarova Nigora Sadriddinovna; Khayrullaev Sardor Shamsiddin ugli (Journals Park Publishing, 2023)
This article presents information on the effect of urea application methods in different rates on soybean variety "Sevinch" on biometric parameters. According to him, it was found that when the plants were exposed to urea at different rates, they had an effect on their biometric indicators, and when the urea rate was increased to 15 grams, all biometric indicators were better than other options.
Keywords: growth, development, urea norms, fertilization, plant number, stem height, number of pods, placement of the first pod.